Improving of Creative Thinking and Learning Outcomes Physics Through Creative Problems Solving (CPS) Approaches - Sulaeha Thayyib (Edumaspul: Jurnal Pendidikan, 2019)
The objective in this research to describing implementation of learning physics using the approach Creative Problem Solving (CPS) to improve creative thinking skills and student’s achievement in class X IPA-1 SMAN 1 Pangsid. The research method applied is Classroom Action Research (CAR) through two learning cycles; each cycle consisted by planning, implementation, observation and reflection. The results showed that learning physics with CPS approach can improve student’s ability to think creatively. After learning undertaken by the CPS approach increased students ability to think creatively and achievement. This is evidenced by: (1) Increasing the number of students who pass out of 12 person in the first cycle to 29 person in the second cycle with an average of 77,39 learning outcomes. N-gainin the first cycle of 0.19 is included in the category of low-and N-gain in the second cycle of 0.30 is included in the medium category, (2) Activity group average student in the learning process are included in the category Activities Fair increased to High Activity category, and (3) The use of creative thinking of students in the first cycle an enough increased to a high in the second cycle. Creative thinking ability of students in teaching physics to provide benefits in solving problems in the community.